Pengaruh Penggunaan Media Visual dalam Pengembangan Bahasa Anak Usia Dini - Nurhasanah Sigalingging; Syamsiah Depalina Siregar (PT. Willy Print Art, 2025)
This study aims to determine the influence of visual media usage in the language development of early childhood at an early childhood education institution in Panyabungan Kota. Visual media such as pictures, posters, flashcards, and educational videos serve as essential tools to stimulate children's language abilities, particularly in vocabulary acquisition, meaning comprehension, and speaking skills. The research employed a quantitative approach with a quasi-experimental design. The subjects were group B children selected purposively from a PAUD (early childhood education center). The research instrument consisted of language development observation sheets used before and after treatment. The results revealed a significant improvement in children's language abilities after the use of visual media in learning activities. Visual media effectively enhanced children's attention, interest, and understanding of the language material delivered. The study concludes that the use of visual media has a positive impact on the language development of early childhood and is recommended as an effective teaching strategy.